Centriole duplication: when PLK4 meets Ana2/STIL. - Kim, M.; Fong, C.S.; Tsou, M.F. (Current Biology, 2014)
Polo-like kinase 4 is known to drive centriole duplication, but the relevant substrate remains elusive. A new study shows that PLK4 phosphorylates a key centriolar component, Ana2/STIL, to initiate centriole assembly.